"Knuckle Cracking": Can Blinded Observers Detect Changes with Physical Examination and Sonography?. Issue 4 (April 2017) - Boutin, Robert D.; Netto, Anuj P.; Nakamura, David; Bateni, Cyrus; Szabo, Robert M.; Cronan, Michael; Foster, Brent; Barfield, William R.; Seibert, Anthony J.; Chaudhari, Abhijit J.
Abstract: Background: Voluntary knuckle cracking is a common habit, with a reported prevalence of 25% to 45%. Habitual knuckle cracking also is a frequent source of questions for physicians, and the largest study to date reported an association with functional hand impairments. Questions/purposes: (1) When compared with subjects who are not habitual knuckle crackers, do habitual knuckle crackers have greater QuickDASH scores, swelling, weakness, joint laxity, or ROM? (2) In subjects who crack their knuckles, does cracking immediately increase ROM? (3) What are the characteristic sonographic findings in joints that crack? Methods: A prospective, institutional review board‐approved study was performed on 400 metacarpophalangeal joints (MPJs) in 40 asymptomatic adult subjects. Of those, 30 subjects had a history of habitual knuckle cracking (defined as daily voluntary popping of MPJs). Clinical history provided by all subjects included a standardized QuickDASH questionnaire. Physical examination was performed by two orthopaedic surgeons (blinded to subjects' knuckle‐cracking history and sonographic outcomes). The physical examination included evaluation for swelling, grip strength, and ROM before and after attempted knuckle cracking. Sonographic examination was conducted by one sonographer, with static and real‐time cine images recorded before, during, and after MPJ distraction was performed by the subjects. Two musculoskeletal radiologists (blinded to subjects' knuckle‐cracking history) interpreted the images for a definite hyperechoic focus during and after MPJ distraction; this was compared against the reference standard of an audible "crack" during joint distraction. Results: Comparing subjects with knuckle cracking with those who did not crack their knuckles, there was no differences in QuickDASH scores (knuckle crackers, 3.7 ± 5.2; nonknuckle crackers, 3.2 ± 6.3; mean difference, 0.6; 95% CI, −3.5 to 4.6; p = 0.786), laxity (knuckle crackers, 2.0 ± 1.8; nonknuckle crackers, 0.3 ± 0.7; mean difference, 1.7; 95% CI, 0.5‐2.9; p = 0.191), and grip strength (preultrasound, right hand, p = 0.499, left hand p = 0.575; postultrasound, right hand p = 0.777, left hand p = 0.424); ROM comparisons between subjects with a history of habitual knuckle cracking versus subjects without such a history only yielded increased ROM in joints that cracked during manipulation (knuckle cracking, 143.8° ± 26.5°; nonknuckle cracking, 134.9° ± 28.6°; mean difference, 9.0°; 95% CI, 2.9°‐15.1°; p = 0.004). Swelling was not observed in any subjects, including when comparing MPJs before versus after distraction maneuvers that resulted in audible cracks. Immediately after a documented crack, there were greater ranges of motion with active flexion (preultrasound, 85.7° ± 12.4°; postultrasound, 88.6° ± 11.6°; mean difference, −2.9°; 95% CI, −5.1° to −0.8°; p = 0.009), passive flexion (preultrasound, 96.1° ± 12.4°; postultrasound, 100.3° ± 10.4°; mean difference, −4.3°; 95% CI, −6.2° to −2.3°; p < 0.001), passive extension (preultrasound, 41.8° ± 18.1°; postultrasound, 45.2° ± 17.6°; mean difference, −3.5°; 95% CI, −6.9° to −0.1°; p = 0.046), and passive total ROM (preultrasound, 137.8° ± 24.8°; postultrasound, 145.6° ± 23.1°; mean difference, −7.7°; 95% CI, −11.7° to −3.8°; p < 0.001). The characteristic sonographic finding observed during cracking events is an echogenic focus that appears de novo dynamically in the joint during distraction. Conclusions: We found no evidence of immediate adverse physical examination findings after knuckle cracking. However, we did find a small increase in ROM among joints that cracked compared with those that did not. Future studies should examine if there are any long‐term beneficial and adverse clinical outcomes associated with habitual knuckle cracking. Level of Evidence: Level I, prognostic study.